Measuring success: The impact of social engineering adaptation on Indonesia’s village development index (IPD) in tourism contexts - Daniel Harapan Parlindungan Simanjuntak; Supsiloani Supsiloani; Muhammad Iqbal; Zanrison Naibaho; Dwiki Li; Cristho David Mangasi Siregar; Manuel Paian Desmon Siallagan (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
This study addresses the deficit in social capital and community participation as primary challenges to sustainable rural tourism. By challenging the dichotomy between 'given' and 'chosen' social capital, this research positions social engineering as a measurable, exogenous variable for optimizing community assets. Using a mixed-methods approach in the Bukit Lawang case study, the research combines thematic analysis of interviews and Focus Group Discussions (FGDs) with quantitative verification through the Village Development Index (VDI). Findings confirm that social engineering, specifically the formation of Pokdarwis successfully transformed traditional gotong royong into productive collaboration and strengthened communal trust. This qualitative shift is validated by significant VDI increases in the Economic (+24), Environmental (+25), and Political (+23) sectors. The study concludes that social capital is a necessary ontological precursor to effective physical investment. The resulting Replicable Model recommends mandating social engineering as a front-loaded strategy to ensure resilient, equitable, and sustainable performance, asserting that engineered social capital is a prerequisite for village-level democratization and policy legitimacy.